Respuesta :

Louli
Answer:
-73 / 28

Explanation:
First, we will get the common denominator for both numbers:
Common denominator = 4*7 = 28

The first given number is 6/-7 which can be written as -6/7
This number is equal to -24/28 .........> I

The second given number is -7/4
This number is equal to -49/28..........>

Now, since I and II have the same denominators, we can simply do the arithmetic operation as follows:
-24/28 + (-49/28) = -24/28 - 49/28
                            = (-24-49) / 28
                            = -73 / 28

Hope this helps :)